TOEFL PBT Training for Vocational Students - Romadhon, Romadhon (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
English is a crucial international language for global communication, science, technology, business, and culture. Being fluent in English opens doors to personal and professional success. The TOEFL (Test of English as a Foreign Language) is a standardized test that measures English language competency in various contexts, including academic and professional. It consists of four parts: Reading, Listening, Writing, and Speaking. TOEFL is essential for vocational student graduates, especially students, who seek work, study abroad, or participate in exchange programs. It also increases the chances of getting a scholarship, as many educational institutions and international scholarship programs require good TOEFL results. In the world of work, English language competency is often required by multinational companies, giving workers a competitive advantage in international business, trade, diplomacy, and technology. Piksi Input Serang Polytechnic requires D3 student graduates to have a TOEFL score above 450 to ensure adequate mastery of English in the international world. A TOEFL PBT training was held for vocational students via the Zoom Meeting platform, using lecture, discussion, and question and answer methods.